International product policy - Boukersi, Lakhdar (Henry Stewart Talks, 2009)
International product strategies: standardization versus modification and localization versus adaptation, Reasons for product modification, Modularization and postponement techniques, Global packaging and labeling, Global product-communication strategies, Global branding decisions, Country of origin effect on brands, Brand counterfeiting